OculoMotor Assessment Tool Test Procedure and Normative Data. Issue 6 (June 2021) - Yaramothu, Chang; Morris, Christopher J.; d'Antonio-Bertagnolli, John Vito; Alvarez, Tara L.
Abstract : SIGNIFICANCE: This study establishes normative data and a testing procedure for the oculomotor assessment tool. The oculomotor assessment tool standardizes visual targets for the Vestibular/OculoMotor Screening assessment and provides additional metrics that may aid in the differentiation between those with normal and those with abnormal oculomotor function potentially caused by a concussion. PURPOSE: This study aimed to assess the oculomotor endurance of healthy participants with no self-reported history of concussions using the oculomotor assessment tool. METHODS: Healthy participants (n = 376, average age of 20.4 years, range of 11 to 34 years, with no self-reported history of concussions) were recruited to perform the following three tasks for 60 seconds each: (1) horizontal saccades, (2) vertical saccades, and (3) vergence jumps. The participants were instructed to alternate visual fixation between two targets for each of the tasks as fast as they could without overshooting or undershooting the visual target. The differences in the number of eye movements between the initial and latter 30 seconds of the 1-minute test were analyzed. RESULTS: A statistical difference ( P < .001) was observed in the number of eye movements for all three tasks (horizontal saccades [70 ± 15 for initial 30 seconds, 63 ± 13 for latter 30 seconds], vertical saccades [68 ± 14, 63 ± 13], and vergence jumps [43 ± 11, 39 ± 10]) between the initial and latter 30 seconds. No significant differences were identified in the number of eye movements or the change in eye movements between the initial and latter 30 seconds based on sex. CONCLUSIONS: These results establish a normative database for various eye movements. These data could potentially be used to compare different patient populations who have binocular endurance dysfunctions potentially due to traumatic brain injury, such as patients with concussion(s).